2021
DOI: 10.1002/jpen.2055
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Anticoagulation Prophylaxis for Catheter‐Related Thrombosis in Pediatric Intestinal Failure: Comparison of Short‐ Vs Long‐Term Treatment Protocols

Abstract: Introduction: Catheter-related thrombosis (CRT) is a devastating complication of central venous catheters in children with intestinal failure (IF), but the optimal preventive therapy of CRT is unknown. This study assessed the efficacy and safety of 2 protocols of secondary anticoagulation prophylaxis with low-molecular-weight heparin (LMWH). Methods: This is a comparative cohort study of children from 2 IF programs who received secondary anticoagulation prophylaxis with LMWH for CRT. The short-term protocol gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…McLaughlin et al reported no bleeds in a cohort of 18 children treated with secondary prophylactic anticoagulation for ≤18 months after the start of anticoagulation 24 . Schmidt et al reported on the effect of short‐term (≤3 months) or long‐term (until line removal) anticoagulation after thrombosis and found that 15% of patients (2 of 13) in the short‐term and 8% of the patients in the long‐term group (2 of 26) experienced a clinically relevant nonmajor bleed 25 . Klaassen et al performed a systematic review on the safety of prophylactic LMWHs used in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McLaughlin et al reported no bleeds in a cohort of 18 children treated with secondary prophylactic anticoagulation for ≤18 months after the start of anticoagulation 24 . Schmidt et al reported on the effect of short‐term (≤3 months) or long‐term (until line removal) anticoagulation after thrombosis and found that 15% of patients (2 of 13) in the short‐term and 8% of the patients in the long‐term group (2 of 26) experienced a clinically relevant nonmajor bleed 25 . Klaassen et al performed a systematic review on the safety of prophylactic LMWHs used in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…24 Schmidt et al reported on the effect of short-term (≤3 months) or long-term (until line removal) anticoagulation after thrombosis and found that 15% of patients (2 of 13) in the short-term and 8% of the patients in the long-term group (2 of 26) experienced a clinically relevant nonmajor bleed. 25 Klaassen et al performed a systematic review on the safety of prophylactic LMWHs used in pediatric patients. They showed that in 18 studies on 1286 children, eight major bleeding events (0.6%; 95% CI, 0.2%-1.0%) were reported; no duration of follow-up is described.…”
Section: Discussionmentioning
confidence: 99%
“…When looking at individual studies published after publication of the meta-analysis, ranging prevalences have been reported. Asouzo et al reported one or more thrombi in 30 patients from a cohort of 65 patients with IF (46%) with a median age of 6.83 years ( 20 ), while Schmidt et al reported thrombosis in 95 out of 388 patients with IF (24%) during a median follow-up time of 398 days ( 21 ). Secondary (i.e., recurrent) VTE occurred in 44% of the patients of the latter study.…”
Section: Incidencementioning
confidence: 99%
“…However, in the new NASPGHAN recommendations (from 2021), the authors state that children with incomplete resolution of thrombus should be maintained on prophylactic anticoagulation with LMWH ( 71 ). Schmidt et al retrospectively compared two different regimens for secondary anticoagulation prophylaxis with LMWH in two pediatric IF centers ( 21 ). In the short-term regimen, children with CVT received therapeutic dosing until thrombus resolution or up to 3 months without prophylactic dosing thereafter, and in the long-term regimen, therapeutic dosing was given up to 3 months and prophylactic dosing continued thereafter until line removal.…”
Section: Managementmentioning
confidence: 99%
“…There was no significant association between anticoagulation dose and bleeding. Schmidt et al also looked at secondary prophylaxis for CADVT among children dependent on total parenteral nutrition [34 ▪ ]. They found that children with history of CADVT had lower recurrence rates if they were continued indefinitely on prophylactic anticoagulation than if they only received anticoagulation for 3 months after the previous thrombosis.…”
Section: Prevention Of Central Venous Catheter-associated Deep Vein T...mentioning
confidence: 99%